Programs as visual, interactive documents. (22nd January 2013) - French, G.W.; Kennaway, J.R.; Day, A.M.
SUMMARY We present a novel approach to combined textual and visual programming by allowing visual, interactive objects to be embedded within textual source code and segments of source code to be further embedded within those objects. We retain the strengths of text‐based source code, while enabling visual programming where it is beneficial. Additionally, embedded objects and code provide a simple object‐oriented approach to adding a visual form of LISP‐style macros to a language. The ability to freely combine source code and visual, interactive objects with one another allows for the construction of interactive programming tools and experimentation with novel programming language extensions. Our visual programming system is supported by a type coercion‐based presentation protocol that displays normal Java and Python objects in a visual, interactive form. We have implemented our system within a prototype interactive programming environment called 'The Larch Environment'. Copyright © 2013 John Wiley & Sons, Ltd.